2014
DOI: 10.1080/14786419.2014.984184
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a new lycodine alkaloid from Lycopodium japonicum

Abstract: A new lycodine alkaloid, N-methylhydroxypropyllycodine (1), was isolated from the club moss Lycopodium japonicum Thunb, together with five known compounds, N-methyllycodine (2), huperzinine (3), β-obscurine (4), α-obscurine (5) and des-N-methyl-α-obscurine (6). Their structures were elucidated by spectroscopic analyses, including 2D NMR techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…(18 S )‐Hydroxypropyllycodine ( 5 ) and (18 S )‐ N ‐methylhydroxypropyllycodine ( 6 ) possess the molecular formula C 19 H 28 N 2 O and C 20 H 30 N 2 O, respectively, obtained from the HR‐ESI‐MS data. Analysis of the 1D NMR data and HSQC spectrum of 5 & 6 (Table 2) resolved identical structures respective to hydroxypropyllycodine [23] and N ‐methylhydroxypropyllycodine [23] . Conclusion of the above was confirmed by the 1 H− 1 H COSY and HMBC data (Figure 2).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…(18 S )‐Hydroxypropyllycodine ( 5 ) and (18 S )‐ N ‐methylhydroxypropyllycodine ( 6 ) possess the molecular formula C 19 H 28 N 2 O and C 20 H 30 N 2 O, respectively, obtained from the HR‐ESI‐MS data. Analysis of the 1D NMR data and HSQC spectrum of 5 & 6 (Table 2) resolved identical structures respective to hydroxypropyllycodine [23] and N ‐methylhydroxypropyllycodine [23] . Conclusion of the above was confirmed by the 1 H− 1 H COSY and HMBC data (Figure 2).…”
Section: Resultssupporting
confidence: 52%
“…(18S)-Hydroxypropyllycodine 2) resolved identical structures respective to hydroxypropyllycodine [23] and N-methylhydroxypropyllycodine. [23] Conclusion of the above was confirmed by the 1 HÀ 1 H COSY and HMBC data (Figure 2). Meanwhile, we obtained the crystal of 6 and determined its relative configuration (Figure 4).…”
Section: Resultsmentioning
confidence: 84%
“…To date, researchers have only used conventional methods to obtain the bioactive alkaloids of Lycopodiaceae and Amaryllidaceae. However, a number of papers have been published using different organic solvents such as methanol, ethanol, hexane, chloroform and many others at various concentrations [14,15]. The application of these solvents has led to the isolation of alkaloids and confirmation of many of their properties, including anti-AChE activity.…”
Section: Methods Of Isolationmentioning
confidence: 99%
“…Huperzine A has a high potential for the treatment of Alzheimer Disease (AD) [2][3][4][5]. Another prominent species is Lycopodium clavatum in which many high potency alkaloids have been found, to name a few: Hupezine E, α-Onocerin, α-obscurine, des-N-methyl-α-obscurine,… [6,7].…”
Section: Introduction *mentioning
confidence: 99%
“…Chuong et al has found a new alkaloid: lycosquarosine A in Vietnamese sourced Huperzia squarrosa [11]. Lycopodium japonicum, a species common in Japan and China, has a unique structure alkaloid group named lycojaponicumins [12], in 2015 another alkaloid: N-methylhydroxypropyllycodine was discovered [7]. Lycopodium clavatum is one of the most widespread species in the family Lycopodiaceae and abundantly found in various area.…”
Section: Introduction *mentioning
confidence: 99%